PENDETEKSIAN LAPORAN KEUANGAN MELALUI FAKTOR RESIKO, TEKANAN DAN PELUANG (BERDASARKAN PRESS RELEASE OJK 2008-2012) - Noval Dwi Aditya Nugraha; Deliza Henny (Jurnal Akuntansi Trisakti, 2015)
This study aims to obtain empirical evidence about the effectiveness of the fraudtriangle is the pressure, opportunity, and rationalization in detecting fraudulentfinancial statements. Based on the theory of fraud triangle Cressey adopted in SAS 99. The variables of the fraud triangle that is used is the pressure that consists of financial stability is proxied by AGROW, external pressures are proxied by LEV, a proxy for managerial ownership OSHI, a proxy for the financial targets ROA, liquidity proxied by (WCTA) and capital turnover is proxied by (SATA); and opportunities which consists of monitoring the effectiveness of control is proxied by IND. Detection of financial statement fraud in this study obtained from the annual report and press releases OJK during 2008-2012 as the dependent variable The population of this study is that non-financial companies listed on the Indonesia Stock Exchange 2008-2012. The total sample of this study is 130 firms, consisting of 13 companies who violate the OJK rules that contain elements of fraud, and being penalized, and the 13 companies that did not commit fraud financial report (based on the type of industry and total assets are equal). Hypothesis testing using logistic regression method. The results of this study indicate that external pressures and financial targets, has significant effect on the financial statement fraud, while financial stability, managerial ownership, liquidity, capital turnover, effectiveness of supervision, does not affect the financial fraud